2012
DOI: 10.1063/1.4721673
|View full text |Cite
|
Sign up to set email alerts
|

Pinned and unpinned epitaxial graphene layers on SiC studied by Raman spectroscopy

Abstract: The study of epitaxial graphene layers grown on SiC by two techniques, namely, the traditional Si sublimation method and the recent chemical vapor deposition (CVD) using temperature induced shift of the Raman 2D line, is presented. The measurements of thermal shift rate of 2D line on 4 H-SiC(0001) allowed us to determine notable differences in interaction of graphene with SiC substrate. The obtained results show that graphene layers grown by Si sublimation of 4 H-SiC(0001) are pinned strongly to the substrate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…shown that the first order temperature coefficient is related to the interaction between the silicon carbide substrate and the epitaxial graphene as v was larger for pinned layers prepared by sublimation method compared to unpinned CVD graphene. 33 The position of SnSe 2 A 1g mode decreases by about 3.5 cm À1 when temperature increases from 70 K to 400 K. The temperature dependence of this mode is more sensitive to a temperature change than in case of any of ReSe 2 modes. The determined first order temperature coefficient v of A 1g was À0.0129 cm À1 /K and was comparable to the values for other layered nanomaterials.…”
mentioning
confidence: 88%
“…shown that the first order temperature coefficient is related to the interaction between the silicon carbide substrate and the epitaxial graphene as v was larger for pinned layers prepared by sublimation method compared to unpinned CVD graphene. 33 The position of SnSe 2 A 1g mode decreases by about 3.5 cm À1 when temperature increases from 70 K to 400 K. The temperature dependence of this mode is more sensitive to a temperature change than in case of any of ReSe 2 modes. The determined first order temperature coefficient v of A 1g was À0.0129 cm À1 /K and was comparable to the values for other layered nanomaterials.…”
mentioning
confidence: 88%
“…Additionally, the graphene multilayers may be oriented in many stacking sequences 14 . A difference between the graphene growth on SiC by the sublimation and the CVD process is pronounced 15 . Very recent analysis of the experimental parameters in the CVD growth of the graphene and graphite sheets has been reported 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Grodecki et al [123] studied the difference between the two processes. Such a difference was explained in terms of growth kinetics.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%
“…There is a lot of excellent reports in literature dealing with deposition of graphene from external sources on metallic surfaces (Cu, Ni, Ir, etc) and on dielectric wafers (SiC, sapphire, Si, etc.). Following the main purpose of this review paper, we focus only on the CVD and MBE growth of graphene on silicon carbide [114,121,[123][124][125][126][127][128][129][130][131][132][133][134][135][136][137][138][139][140][141]. Therefore, the aim of this subsection is twofold: (i) to understand the main difference between thermal decomposition of silicon carbide and bottom-up growth of graphene on SiC and (ii) to extensively review the literature concerning the CVD and MBE growth processes with participation of SiC substrate.…”
Section: Growth Of Graphene On Sic Using External Sourcesmentioning
confidence: 99%